Determining The Relationship Between Professional Self-Esteem and Professional Commitment in Nurses - Şefika Dilek Güven; Ayla Ünsal (Association of Nurse Managers, 2022)
Aim: The study aims to determine the relationship between professional self-esteem and professional commitment of nurses. Method: The study is a correlational descriptive study. 257 nurses constituted the sample of the study. The data were collected with the information form, the Professional Self-Esteem Scale, and the Nursing Professional Commitment Scale. Data were evaluated with descriptive statistics, independent sample t-test,one-way ANOVA, and Pearson correlation test. Results: The total mean score of the nurses' Professional Self-Esteem Scale was 89.01+-11.97, and the total mean score of the Nursing Professional Commitment Scale was calculated as 63.98+-10.11. It was determined that nurses who chose the profession voluntarily did not choose the profession voluntarily, nurses who were satisfied with their profession had a higher total mean score on Professional Self-Esteem Scale than those who were not satisfied with their profession, and nurses who were satisfied with their profession had a higher total mean score on Nursing Professional Commitment Scale than those who were not satisfied with their profession. A statistically significant difference was found between nurses' total scores of Professional Self-Esteem Scale according to their willingness to choose the profession and their satisfaction with the profession, and between the total score of the Nursing Professional Commitment Scale according to their satisfaction with the profession. A positive and moderately statistically significant relationship was determined between the total scores of Professional Self-Esteem Scale and the Nursing Professional Commitment Scale. Conclusion: The findings of the study revealed that nurses' professional self-esteem and commitment to the profession should be brought to a sufficient level.